Time discounting and the body mass index - Lex Borghans; Bart H. H. Golsteyn (Institute for the Study of Labor (IZA), 2005)
In many Western countries, the relative weight of people - measured by the Body Mass Index (BMI) - has increased substantially in recent years, leading to an increasing incidence of overweight and related health problems. As with many forms of risky behavior, it is plausible that overweight is related to the individual discount rate. Increases in credit card debts, the rise in gambling and the development of a more hedonic life style, suggest that the average discount rate has increased over time. This increase may have been the cause of the increase in BMI. Applying a large set of indicators for the individual discount rate, this paper analyzes whether changes in time discounting can account for differences in body mass between individuals at a given point in time and whether changes in the average individual discount rate can explain the remarkable increase in BMI experienced in recent years. We find some evidence for a link between time discounting and differences in BMI between people, but this relationship depends strongly on the choice of the proxy for the discount rate. Giving our hypothesis the best chance, we analyze the development of the time discounting proxies that are most strongly related to BMI. We find no evidence for a change of these proxies over time. Our main conclusion therefore is that overweight might be related to the way people discount future health benefits, but the increase in BMI has to be explained by shifts in other parameters that determine the intertemporal decisions regarding the trade-off of current and future health and satisfaction.
Keywords: I1; 330; body mass index (BMI); risky behavior; time discounting